A Framework for Testing Query Transformation Rules - Narasayya, Vivek; Ramamurthy, Ravi; Elmongui, Hicham (Association for Computing Machinery, Inc., 2009)
In order to enable extensibility, modern query optimizers typically leverage a transformation rule based framework. Testing individual rule correctness as well as correctness of rule interactions is crucial in verifying the functionality of a query optimizer. While there has been a lot of work on how to architect optimizers for extensibility using a rule based framework, there has been relatively little work on how to test such optimizers. In this paper we present a framework for testing query transformation rules which enables: (a) efficient generation of queries that exercise a particular transformation rule or a set of rules and (b) efficient execution of corresponding test suites for correctness testing.